2003
DOI: 10.1046/j.1523-1755.2003.00022.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus–related cryoglobulinemic glomerulonephritis: Long-term remission after antiviral therapy

Abstract: Antiviral therapy with IFN-alpha and ribavirin may be considerably beneficial in patients with HCV-related CGN who obtain sustained virologic response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(46 citation statements)
references
References 22 publications
0
45
0
1
Order By: Relevance
“…After discontinuation of therapy, both recurrence of viremia and proteinuria were observed. Other studies (38,39) have demonstrated an improvement in HCV-related renal disease associated with response to treatment, supporting a direct relationship between HCV infection and renal disease.…”
Section: Summary Of Findingsmentioning
confidence: 97%
“…After discontinuation of therapy, both recurrence of viremia and proteinuria were observed. Other studies (38,39) have demonstrated an improvement in HCV-related renal disease associated with response to treatment, supporting a direct relationship between HCV infection and renal disease.…”
Section: Summary Of Findingsmentioning
confidence: 97%
“…In patients with HCV-associated renal disease, sustained virologic responses (SVR) to antiviral therapy have been associated with improvements in renal histology (reduced glomerular inflammation and immune deposits) and in biochemical markers of renal function (49). However, the clinical and histologic improvements are not seen uniformly.…”
Section: Hcv-associated Posttransplantation Glomerulopathiesmentioning
confidence: 98%
“…Treated patients typically demonstrate improvements in renal function and reduced levels of cryoglobulins. Although early reports indicated a high rate of relapse after IFN discontinuation, relapse rates seem to have declined after ribavirin was used in combination with IFN (49,64,124).…”
Section: Management Of Hcv-associated Renal Disease After Transplantamentioning
confidence: 99%
See 2 more Smart Citations